Appendicitis in epigastric hernia: a rare case report - Fonseca, Bárbara da Silva Oliveira; Origa, Luís Gustavo; de Queiroz Junior, José Reinaldo Ribeiro; Faria, Lucas Azevedo; Martins, Fábio Pimentel; de Guimarães, Rodrigo Loiola; Lima, Guilherme Augusto Nunes Correa; Lisboa, Thiago Assis (International Surgery Journal, 2018)
Epigastric hernias are defined as defects in the abdominal midline between the navel and the xiphoid process. Incarceration and strangulation are rare. This is a case report, the purpose of this article is to report a case of acute appendicitis successfully treated in an incarcerated epigastric hernia at the Santa Casa de Misericórdia Hospital in Belo Horizonte, correlating with the current literature. It is not yet clear how the cecum and appendix can mobilize freely to the epigastric region and present within the sac of an epigastric hernia. It has been suggested that in 10% of the population, there may be anatomical variation and abnormal mobility of the cecum, referred to as mobile cecal syndrome. However, it is difficult to establish which pathophysiological process (or perhaps both) could have attributed to this rare presentation.